Investigation of flow over oscillating NACA 4421airfoils in tandem configuration at low Reynolds number - Airil Seet Azry Seet (2019)
The present study is on the experimental investigation of the flow over oscillating NACA4421 airfoils in various tandem configurations at low Reynolds number of 8.6 x 103. Force and two dimensional particle image velocimetry (PIV) measurements were carried out in the NTU closed loop water tunnel with a freestream velocity, U∞ = 0.102m/s. The effects of phase angle, ϕ, stagger distance, Sd (= x/c where x is the horizontal axial spacing between the tandem airfoils and c is the chord) and gap, G (= |y|/c, where y is the vertical spacing between the tandem airfoils) were investigated for both oscillating and static tandem airfoils. In-phase oscillating tandem configuration has shown its potential to increase average combined lift coefficient, CL up to 47.7% but resulted in a corresponding increase in average combined drag coefficient, CD up to 54% at α > ±30˚ in relation to the single oscillating case. It also attained its best combined CL / CD ratio of 2.33 which is 35% lower than the single oscillating airfoil at α = ±45˚ with Sd of 2. This is attributed to the in-phase oscillating downstream airfoil’s ability to generate 89% higher average CL than the single oscillating airfoil as a result of the down-washed vortex interaction between the primary shed vortex before its first stroke reversal. However, this interaction increases the average CD up to 5 times more than the single oscillating airfoil which decreases the combined CL / CD ratio for the in-phase oscillating tandem configuration. The out-of-phase tandem oscillating configuration produces the highest combined CL / CD ratios at larger α > ±30˚ with the larger Sd of 2.5 due to the downstream airfoil’s ability to generate large lift improvements of more than 100% and exhibiting comparable drag production in relation to the single oscillating airfoil through effectively capitalizing on its ‘indirect’ down-washed vortex interaction effects. Thus, making the out-of-phase oscillating tandem configuration at Sd = 2.5 the most ideal configuration in the present study, potentially viable for hovering flight.